The problem of random housing in the city of Baghdad and the methods used to solve it For the period (1930-2012 AD) (Journal of the College of Basic Education, 2022)
Most countries of the world face the phenomenon of slums (illegal housing), especially in their urban-rural outskirts or in empty and unexploited areas within the basic designs of cities.